The Impact of Nonverbal Communication on Effective Public Speaking in English - Jasuli Jasuli; Sri Fatmaning Hartatik; Endang Setiyo Astuti (UIBU, 2024)
Nonverbal communication (NVC) plays a crucial role in effective public speaking, particularly for English language learners (ELLs) who may face unique challenges in navigating both linguistic and cultural aspects of communication. This study is carried out through a literature review method, following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines, to examine the impact of NVC on public speaking among ELLs in higher education settings, and synthesize findings from diverse studies. The review reveals that effective use of NVC significantly enhances perceived credibility, audience engagement, and message clarity for ELLs. Specific nonverbal behaviors, such as maintaining eye contact, using open gestures, and adopting a confident posture, are associated with increased speaker effectiveness. Additionally, the literature highlights the importance of cultural sensitivity in NVC instruction, as nonverbal cues can carry different meanings across cultures. The findings underscore the need for explicit instruction in NVC strategies within English language curricula, emphasizing cultural responsiveness and creating inclusive learning environments that empower ELLs to become confident and effective communicators. This review contributes to the growing body of research on NVC in educational contexts and offers practical implications for English language educators seeking to enhance their students' public speaking skills.